Analisis Fungsi Pengelolaan Sistem Pendidikan Dan Permasalahannya “Studi Kasus Kesenjangan Kompetensi Guru Di SMA” - Indra Puspita Sari; Wiji Mulyo Maradianto; Jabarullah Jabarullah; Siti Inganah (Peneliti.net, 2026)
This study aims to analyze the implementation of education system management functions and the factors causing teacher competency gaps in high schools. The study used a descriptive qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The results showed that the implementation of education management functions (planning, organizing, actuating, and controlling) has not been running optimally. The main problems include mismatched teacher educational backgrounds, low digital literacy, financial constraints, weak monitoring systems, and low teacher welfare. In addition, overlapping tasks and miscommunication were still found in the implementation of school management. To address these problems, the school implemented several strategic steps such as optimizing BOS funds, peer coaching programs, digital literacy training, academic supervision, and providing performance-based incentives. This study confirms that the integration of education management functions is crucial for improving the quality of education sustainably.